1991
DOI: 10.1016/s0022-5193(05)80313-3
|View full text |Cite
|
Sign up to set email alerts
|

Size and connectivity as emergent properties of a developing immune network

Abstract: The development of the immune repertoire during neonatal life involves a strong selection process among different clones. The immune system is genetically capable of producing a much more diverse set of lymphocyte receptors than are expressed in the actual repertoire. By means of a model we investigate the hypothesis that repertoire selection is carried out during early life by the immune network. We develop a model network in which possibly hundreds of B cell clones proliferate and produce antibodies followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0
2

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 59 publications
5
72
0
2
Order By: Relevance
“…2 before the global bifurcation involving the unstable manifold of the HH state at p = 3.7. Similar examples in the original coordinate system can be found in De Boer and Perelson (1991). In Fig.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…2 before the global bifurcation involving the unstable manifold of the HH state at p = 3.7. Similar examples in the original coordinate system can be found in De Boer and Perelson (1991). In Fig.…”
supporting
confidence: 65%
“…Conversely, we observed in Part I that the interpretation of the nullclines of the SL coordinate system is not intuitive. Perelson, 1991). Varela (1989, 1990) have also searched for conditions for which oscillatory chaotic behavior could be sustained in the absence of a continuous bone marrow source.…”
Section: -mentioning
confidence: 99%
“…The instability of SLE antibody repertoires, however, suggests some speculation. Previous evidence has indicated that circulating Igs contribute to the selection of the emerging B cell repertoires in the bone marrow [20][21][22], and to the level and repertoire of natural antibodies [23][24][25][26][27]. The surprising conservation of the size and repertoire of natural antibodies in normal individuals also suggests that they are recursively selected, the circulating Ig pool promoting its own dynamic maintenance.…”
Section: Instability Of Sle Antibody Repertoiresmentioning
confidence: 99%
“…Jerne's (1974) hypothesis that the immune system functions by means of a network of idiotypic interactions has been investigated extensively by theoretical biologists. Theoretical models that can account for memory, tolerance and repertoire selection (Hoffmann, 1980;De Boer and Hogeweg, 1989a;Weisbuch et al, 1990;De Boer and Perelson, 1991) have been developed and they have interesting self-organizing properties (De Boer and Perelson, 1991;De Boer et al, 1992aStewart and Varela, 1991).…”
mentioning
confidence: 99%
“…Many recent idiotypic network models are based upon a phenomenological log bell-shaped function determining B cell activation as a function of the total concentration of ligand, or more precisely of the "field" (De Boer, 1988;De Boer and Hogeweg, 1989a, b;Weisbuch et al, 1990;De Boer and Perelson, 1991;De Boer et al, 1992a, b;De Boer et al, 1993a-c;Anderson et al, 1993). This log bell-shaped function is frequently interpreted as a phenomenological description of the fraction of B cell receptors crosslinked by ligand (Perelson, 1984).…”
mentioning
confidence: 99%